Subprime mortgages, foreclosures, and urban neighborhoods - Kristopher S. Gerardi; Paul S. Willen (Federal Reserve Bank of Boston, 2008)
This paper analyzes the impact of the subprime crisis on urban neighborhoods in Massachusetts. The topic is explored using a dataset that matches race and income information from HMDA with property]level, transaction data from Massachusetts registry of deeds offices. With these data, we show that much of the subprime lending in the state was concentrated in urban neighborhoods and that minority homeownerships created with subprime mortgages have proven exceptionally unstable in the face of rapid price declines. The evidence from Massachusetts suggests that subprime lending did not, as is commonly believed, lead to a substantial increase in homeownership by minorities, but instead generated turnover in properties owned by minority residents. Furthermore, we argue that the particularly dire foreclosure situation in urban neighborhoods actually makes it somewhat easier for policymakers to provide remedies.
Keywords: D11; D12; G21; 330; Finanzmarktkrise; Subprime-Hypothek; Zwangsvollstreckung; Wohneigentum; Stadt; Massachusetts